The Effects of Transcranial Direct Current Stimulation (tDCS) Combined With Proprioceptive Training for Blind Individuals: The Study Protocol for a Randomized Controlled Clinical Trial - Parreira, Rodolfo Borges; Lopes, Jamile Benite Palma; França, Milena Santana; Albuquerque, Mayara Bernardo; Cordeiro, Lorraine Barbosa; Cardoso, Deborah Carvalho da Silva; Cimolin, Veronica; Galli, Manuela; Oliveira, Claudia Santos (Frontiers in Neurology, 2020)
To maintain the balance, the postural system needs to integrate the three main sensorial systems: visual, vestibular and somatosensory to keep postural control within the limits of stabilization. The supply of one of these systems, in this case, the vision, will have a great disturbance on the postural control influencing the behavior of the balance, resulting in falls. The aim of this study is to analyze the effects of transcranial direct current stimulation (tDCS) combined with proprioceptive exercises on postural control in individuals with congenital and acquired blindness. In this randomized, controlled, double-blind, clinical trial, male and female individuals with blindness between 18 and 55 years of age will participate in this study will participate in this study divided into three phases: 1 – Determine differences in postural control and gait between individuals with congenital and acquired blindness with and without the use of a guide stick when wearing shoes and when barefoot; 2 – A pilot study to analyze the effects a bilateral cerebellar anodal tDCS on postural on postural control and gait; and 3 – A treatment protocol will be conducted in which the participants will be allocated to four groups: G1 – active tDCS + dynamic proprioceptive exercises; G2 – sham tDCS + dynamic proprioceptive exercises; G3 – active tDCS + static proprioceptive exercises; and G4 – sham tDCS + static proprioceptive exercises. Evaluations will involve a camera system for three-dimensional gait analysis, a force plate, and electromyography. Dynamic stability will be determined using the Timed Up and Go test and static stability will be analyzed with the aid of the force plate. The viability of this study will allow the determination of differences in postural control between individuals with congenital and acquired blindness, the analysis of the effect of tDCS on postural control and the establishment of a rehabilitation protocol.